Microbiome of the mare and the foal at parturition - Konda, Matthew C.; Jones, E.; Kouba, Joann M. (My University, 2019)
The objective of this study was to identify the microbial community in the meconium and to compare it to the microbiome of the mare’s placenta, milk, and feces at parturition. Six mares were used for this study. Mare fecal, milk, placental and foal meconium samples were collected at parturition. The mare and foal fecal matter were obtained by means of a rectal grab with a lubricated, sterile glove. Prior to nursing, a sample of the colostrum was taken after disinfecting the teats with an iodine solution. When the placenta was expelled from the mare, a sample was collected from the internal portion. All samples were frozen after collection until they were analyzed with Next Generation Sequencing techniques. The samples were run through a DNA extraction kit, followed by PCR, and then sequenced using Illumina Miseq. The sequencing data were analyzed using the QIIME bioinformatics pipeline. The foal meconium consisted of a unique microbial community that differs from the microbiome of the mare. In the meconium and placenta, the dominant phylum was Proteobacteria, however Firmicutes and Bacteroidetes were also present within the microbial community at lesser relative abundancies. Firmicutes, Bacteroidetes, and Verrucomicrobia compromised the majority of the phyla in mare feces. Proteobacteria was the dominant phylum in milk. The mare feces were significantly higher (P < 0.05) in microbial diversity when compared with meconium, milk and placental samples. Meconium was greater (P < 0.05) in bacterial diversity than milk, however there was no difference in diversity between meconium and placental samples. In conclusion, the microbial community of the foal meconium shared taxa with both the mare fecal and placental samples. This indicates the possibility that microbes were transferred between the mare and the foal during gestation, however the timing and methods of transport remain unknown.
Keywords: Spring 2019